1998
DOI: 10.1038/sj.jhh.1000654
|View full text |Cite
|
Sign up to set email alerts
|

White coat hypertension and target organ involvement: the impact of different cut-off levels on albuminuria and left ventricular mass and geometry

Abstract: The aim of this cross-sectional study which took place in a hypertension clinic at a district general hospital in Denmark was to make a pragmatic definition of white coat hypertension. A total of 420 patients were referred consecutively from general practice with newly diagnosed untreated essential hypertension and 146 normal subjects were drawn at random from the Danish national register. The following measurements were taken: office blood pressure; 24-h ambulatory blood pressure (BP) monitoring; echocardiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 26 publications
(39 reference statements)
1
11
1
Order By: Relevance
“…[10][11][12]16 In spite of our specific results on the WCH group, this study reveals quite expected overall relations between cardiovascular events and BP data. We found that the event rate was more strongly predicted from ABP than OBP.…”
Section: -Year Follow-up Of Wchcontrasting
confidence: 61%
See 2 more Smart Citations
“…[10][11][12]16 In spite of our specific results on the WCH group, this study reveals quite expected overall relations between cardiovascular events and BP data. We found that the event rate was more strongly predicted from ABP than OBP.…”
Section: -Year Follow-up Of Wchcontrasting
confidence: 61%
“…Baseline evaluation included a detailed medical history, OBP and ABPM; these data have been reported previously. [9][10][11][12][13] All subjects gave their informed consent. The study was conducted in accordance with the second declaration of Helsinki and was approved by the local ethics committee.…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the LVMI was significantly greater in patients with WCH than in controls, a difference which persisted even after secondary matching for 24-h BP, and in a multiple regression model, WCH was the only significant predictor of LVMI. In contrast to Hoegholm et al, 13 the data from Owens et al 11 suggests that changes in left ventricular structure are not entirely accounted for by the level of BP and that other features may distinguish the patient with WCH from the truly normotensive individual. WCH may therefore result in a degree of LVH, which is probably one of the more important indices of hypertensive target organ damage.…”
Section: Association With Target Organ Damagementioning
confidence: 83%
“…Again, the prevalence of LVH ranged from 2.4% (not significantly different from normotensive controls) to 14.7% (P Ͻ 0.05), depending upon the definition used. 5 An alternative approach to this problem was taken by Hoegholm et al 13 who studied left ventricular structure in 420 patients with mild to moderate hypertension. Significant LVH was only present when the ambulatory daytime systolic BP was greater than 135 mm Hg, with no relationship with ambulatory daytime diastolic BP recordings.…”
Section: Association With Target Organ Damagementioning
confidence: 99%